2016
DOI: 10.3389/fmicb.2016.00010
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Application of Synbiotics, a Fusion of Probiotics and Prebiotics, and Biogenics as a New Concept for Oral Candida Infections: A Mini Review

Abstract: Candida is a major human fungal pathogen causing infectious conditions predominantly in the elderly and immunocompromised hosts. Although Candida resides as a member of the oral indigenous microbiota in symbiosis, some circumstances may cause microbial imbalance leading to dysbiosis and resultant oral candidiasis. Therefore, oral microbial symbiosis that suppresses the overgrowth of Candida is important for a healthy oral ecosystem. In this regard, probiotics, prebiotics, and synbiotics can be considered a pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 83 publications
(85 reference statements)
0
36
0
Order By: Relevance
“…Synbiotics are a combination of healthy bacteria or probiotic with a prebiotic, that provides fuel for the probiotic. 101 In a small study in 2004, synbiotic treatment was shown to increase nonurease-producing Lactobacillus species for 14 days following cessation of treatment, leading to a reduction in minimal hepatic encephalopathy. 102 Studies are lacking in patients with alcoholrelated liver disease.…”
Section: Probiotics Prebiotics and Synbioticsmentioning
confidence: 99%
“…Synbiotics are a combination of healthy bacteria or probiotic with a prebiotic, that provides fuel for the probiotic. 101 In a small study in 2004, synbiotic treatment was shown to increase nonurease-producing Lactobacillus species for 14 days following cessation of treatment, leading to a reduction in minimal hepatic encephalopathy. 102 Studies are lacking in patients with alcoholrelated liver disease.…”
Section: Probiotics Prebiotics and Synbioticsmentioning
confidence: 99%
“…Recently, many studies have reported that heat-killed microorganisms or fractionated cellular components, such as cytoplasmic extracts, membrane fragments, exopolysaccharides, and lipoteichoic acids, can modulate various immune responses, alleviating symptoms of colitis, autoimmune disorders, and allergies [20,21]. For this kind of substances, Mitsuoka [22] suggested the term "biogenics," which is defined as "food ingredients which beneficially affect the host by directly immunostimulating or suppressing mutagenesis, tumorigenesis, peroxidation, hypercholesterolemia, or intestinal putrefaction," and includes the administration of nonviable probiotic bacteria to obtain some "probiotic" effects [23]. Biogenic materials, including nonviable probiotic bacteria, have been actively developed as health supplements or functional foods because they possess stability to processes involving heat or acids [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Several species metabolize a large diversity of different carbon sources, including all major categories of oligosaccharides (Ganzle & Follador, 2012). Earlier studies revealed that a variety of probiotic bacterial strains have been incorporated by food industry in different combination with prebiotics that act synergistically to promote gut health (Ho & Prasad, 2013;Ohshima, Kojima, Seneviratne, & Maeda, 2016;Patel & DuPont, 2015).…”
mentioning
confidence: 99%